The case for assessing the full value of new tuberculosis vaccines. Issue 3 (19th March 2020) - Gebreselassie, Nebiat; Hutubessy, Raymond; Vekemans, Johan; den Boon, Saskia; Kasaeva, Tereza; Zignol, Matteo
Tuberculosis (TB) ranks as the leading cause of death among infectious diseases in human history, claiming over a billion lives in the past two centuries alone [1, 2]. Although a number of important advances have been made to control TB in the past decade, an estimated 10 million people fell ill with TB and 1.5 million died from the disease in 2018 alone [1]. The only licensed TB vaccine, bacille Calmette–Guérin (BCG), provides partial protection against severe forms of TB in infants and young children (averting thousands of paediatric deaths annually), but fails to stop transmission of pulmonary tuberculosis in adults [3, 4]. A multidisciplinary framework is needed to guide the research needed for making economic and health impact arguments for tuberculosis vaccine development and uptake http://bit.ly/2stNDok